CONSTITUTIONAL AND LEGAL BASIS OF CIVIL SOCIETY INSTITUTIONS (Neo Scientific Peer Reviewed Journal, 2024)
In the conditions of democratic modernization of our country, constitutional reforms based on national characteristics and international experience were carried out based on the requirements of today's times. In the Constitution of the Republic of Uzbekistan, among other important areas and priorities of our life, the norms related to the formation of an active civil society and the further development of the institution of public control were included. This article describes the constitutional strengthening of the rights, status and powers of civil society institutions. At the same time, in accordance with the Constitution, the main areas of activity of the institutions of civil society are studied.